Biaya Promosi dan Tarif Kamar terhadap Pendapatan Kamar di Hotel THE HAVEN Bali Seminyak - Laurentzia Aureola Octavina Wibowo; I Ketut Sutapa; I Made Gede Darma Susila (Journal Research of Management, 2024)
The study aims to determine the effect (1) promotional fees on room revenue at The Haven Bali Seminyak Hotel (2) room rates on room revenue at The Haven Bali Seminyak Hotel, (3) promotional fees and room rates on room revenue at The Haven Bali Seminyak Hotel, (4) how big the promotional fees and room rates on room revenue at The Haven Bali Seminyak Hotel. This study used secondary data in the form of promotional fees, room rates, and room revenue that earned from 2018 until 2022. This research is using a quantitative approach. Collecting data using interview and documentation. The sample in this study amounted to 60 data used time series data appointed by 2018 January until December 2022. Data analysis used multiple linear regression. The results of the study found that (1) Promotional fees has a positive and significant effect on room revenue, the value of sig. 0,000 < 0,005 indicates that H0 is rejected and Ha is accepted. (2) Room rates has a negative effect on room revenue, the value of sig. 0,831 < 0,005 indicates that H0 is accepted and Ha is rejected. (3) Promotional fees and Room rates together has a positive and significant influence on purchasing decisions. The simultaneous contribution or contribution of Promotional Fees and Room Rates variables to room revenue decisions is 71.9% while 29.1% is determined by other variables not examined in this study.